Efficiency and Comfortability of a Newly Developed Pedal-Operated Reciprocating Pump Device - U. ALONZO, Clark Dave; CELERINOS, Philip Jun Sacote; SANCHEZ-COMPANION, Kristine Domogoy; FLORES, Emilio Joaquin; O. GAHUMAN, Mary Josephine; T. PARCON, Don Rick (Engineering Transactions, 2024)
Insufficient water supply in rural areas has prompted many communities to opt for manually operated water pumps. However, these water pumps can be demanding to operate and may pose physical difficulties for users. This study addresses this issue by developing a pedal-operated water pump with a modified reciprocating piston pump and a seating system that users can comfortably operate for a prolonged period of time. The study tested thirty respondents categorized into three groups based on demographic parameters such as age, weight, and height. Results demonstrated that the newly developed pedal-operated water pump achieved its highest mechanical efficiency of 62.73% and discharge efficiency of 99.50%. Furthermore, the study found that age, weight, and height have a very low correlation with cycling speed, with correlation levels of 3.93%, 1.83%, and 1.83%, respectively. The cycling speed also exhibited a low correlation level of 2.17% with the calories burned by the user. Thus, the developed water pump only required minimal physical effort from users of various age groups to produce adequate water outputs of up to 40.46 liters per minute. This study highlights the efficiency and user convenience of the newly developed pedal-operated water pump, which can be useful in communities for domestic and agricultural water supply.